Ridge Splitting Technique for Horizontal Augmentation and Immediate Implant Placement - Papathanasiou Ioannis; Vasilakos Georgios; Baltiras Sotirios; Zouloumis Lampros (Balkan Stomatological Society, 2014)
Insufficient width of the alveolar ridge often prevents ideal implant placement. Guided bone regeneration, bone grafting, alveolar ridge splitting and combinations of these techniques are used for the lateral augmentation of the alveolar ridge. Ridge splitting is a minimally invasive technique indicated for alveolar ridges with adequate height, which enables immediate implant placement and eliminates morbidity and overall treatment time. The classical approach of the technique involves splitting the alveolar ridge into 2 parts with use of ostetomes and chisels. Modifications of this technique include the use of rotating instrument, screw spreaders, horizontal spreaders and ultrasonic device.